Impact of weather dependent variables on cooling and dehumidification loads of air-conditioned office in warm-humid - Adjei, Eunice Akyereko; Omer, Siddig; Abanyie, Samuel Amos (Penerbit Universiti Kebangsaan Malaysia, 2021)
Dehumidification in buildings remains a dominant contributor to cooling load in hot-humid climate zone irrespective of the cooling technology used, thus consuming much energy and also contributes to environmental impact through emission of greenhouse gases. Benchmarking and control of energy use in the design and the operation of buildings in developing countries come with much challenges. This paper used ESDL TAS Building Simulation Software to perform dynamic simulation to explore the potential reduction of dehumidification and cooling loads of an air-conditioned office building in the hot-humid climate of Ghana through a parametric study of four weather dependent variables. The combined input variables achieved a reduction of 64.28% and 58.12% in dehumidification and cooling loads respectively of the base case model. Tuning the range of the thermostat temperature and relative humidity settings demonstrated significant savings. Reducing infiltration rate arising from all leakages to a practically feasible minimum, as well as ventilation gain demonstrated appreciable savings in energy use. Tuning of vapour diffusion factor of building materials, however, did not have significant effect on the loads. The outcome of the study is expected to inform the design and operation of air-conditioned office buildings in developing countries of hot-humid climate conditions to achieve optimum energy consumption for cooling of spaces.